The Effect of Emotional Intelligence and Organizational Commitment on Service Quality Mediated by Organizational Citizenship Behaviour - Dilla Oktaviana; Rini Safitri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study aims to determine the effect of emotional intelligence and organizational commitment on service quality with organizational citizenship behaviour as a mediation variable. This study is located on BPJS Kesehatan KC Pekalongan, with a total population amounted 75 employees, and the sample is about 40 employees. The sampling technique in this study uses judgment sampling. The analysis technique used path analysis with SPSS 25 as a hypothesis testing tool. The study found that emotional intelligence significantly affects organizational citizenship behaviour. However, organizational commitment hasn’t a significant effect on organizational citizenship behaviour because employees who have a high level of organizational commitment do not always mean that these employees also exhibit OCB behavior. Emotional intelligence, organizational commitment, and organizational citizenship behaviour significantly affect service quality.